A Model of Genre-Based Paragraph Writing Materials for The Second Semester Students of English Education Study Program at Jambi University - Lilik Ulfiati (Universitas Jambi, 2017)
Writing is as essential language skill that require the college students to be able to have good language learning. The aim of this research is to develop supplementary Paragraph Writing materials in behalf with Genre-Based Approach (GBA) as the underpinning instructional theory. This research focus on arising problem out here is: How is a model of genre based paragraph writing materials for the second semester students of English Education Study Program at Jambi University developed? In this research, research and development (R&D) was the type of research. In addition, the researcher caries out a series of data in which the earlier data collecting by interviewing the six students and it is followed by analyzingparagraph writing syllabus and writing samples to collect more data and information. The participants of this research are the six students at thefourth semester students of English Education Study Program at Jambi University. The research indicated that the second semester students need to learn three topics of paragraph writing materials they are; 1) descriptive, 2) cause and effect, and 3) comparison and contrast paragraph. When the analysis stage and design stage have done by the researcher. The researcher continued the development stage by involving the learning materials and design validator who validate the validity of the product. Then the product is tested by the six students as the users of this product. In conclusion, the researcher continue to evaluate the product’s weaknesses.